Strengthening Local Industrial Ecosystems: Potentials and Challenges of IKM Development in North Sumatra - Hasanah, Uswatun; Faried, Annisa Ilmi; Sembiring, Rahmad (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study evaluates the readiness and competitiveness of Small and Medium Industry (IKM) clusters across districts and cities in North Sumatra using a structured scoring model that assesses six key dimensions: institutional and legal capacity, production and human resources, market access and competitiveness, sustainability and development, and linkages to Special Economic Zones (KEK) and Industrial Estates (KI). The analysis, based on quantitative scoring complemented by qualitative insights, reveals significant disparities in cluster performance. Leading clusters such as the Simalungun Coffee Cluster and the Serdang Bedagai Pandan Weaving Cluster demonstrate strong institutional frameworks, high production capacity, product innovation, and established market linkages. Meanwhile, developing and potential clusters exhibit moderate performance but require improvements in technology adoption, product diversification, and market expansion. Clusters in the guidance category face fundamental challenges, including weak institutional structures, limited production capabilities, and minimal access to broader markets. Overall, the findings highlight the critical role of institutional strengthening, technological upgrading, and market integration as core strategies for cluster development. The study recommends a phased and targeted development approach tailored to each cluster’s readiness level to enhance regional competitiveness and support sustainable industrial growth in North Sumatra.